Finite Element Model for Cardiac Cell mechano-electrical stimulation - Urdeitx Diaz, Pau; Doweidar, Mohamed H. (Jornada de Jóvenes Investigadores del I3A, 2020)
Cardiomyocyte behavior is highly dependent on the mechanical and electrical stimuli. We present a computational model, based on the FEM, to evaluate their behavior under electro-mechanical stimulation. Cell migration, adhesion, and collective behavior have been considered. Low stiffness and high alternating electric field have shown to be the best combination.